HIV and aging: state of knowledge and areas of critical need for research. A report to the NIH Office of AIDS Research by the HIV and Aging Working Group. - High, Kevin P; Brennan-Ing, Mark; Clifford, David B; Cohen, Mardge H; Currier, Judith; Deeks, Steven G; Deren, Sherry; Effros, Rita B; Gebo, Kelly; Goronzy, Jörg J; Justice, Amy C; Landay, Alan; et al. (Journal of acquired immune deficiency syndromes (1999), 2012)
HIV risk behaviors, susceptibility to HIV acquisition, progression of disease after infection, and response to antiretroviral therapy all vary by age. In those living with HIV, current effective treatment has increased the median life expectancy to >70 years of age. Biologic, medical, individual, social, and societal issues change as one ages with HIV infection, but there has been only a small amount of research in this field. Therefore, the Office of AIDS Research of the National Institutes of Health commissioned a working group to develop an outline of the current state of knowledge and areas of critical need for research in HIV and Aging; the working groups' findings and recommendations are summarized in this report. Key overarching themes identified by the group included the following: multimorbidity, polypharmacy, and the need to emphasize maintenance of function; the complexity of assessing HIV versus treatment effects versus aging versus concurrent disease; the inter-related mechanisms of immune senescence, inflammation, and hypercoagulability; the utility of multivariable indices for predicting outcomes; a need to emphasize human studies to account for complexity; and a required focus on issues of community support, caregivers, and systems infrastructure. Critical resources are needed to enact this research agenda and include expanded review panel expertise in aging, functional measures, and multimorbidity, and facilitated use and continued funding to allow long-term follow-up of cohorts aging with HIV.
Keywords: Aged; Aging; Anti-HIV Agents; Biological Markers; Comorbidity; Health Services Needs and Demand; Health Services Research; HIV Infections; Humans; Middle Aged; Needs Assessment; Polypharmacy